2022
DOI: 10.1136/jmg-2022-108655
|View full text |Cite
|
Sign up to set email alerts
|

A digital pathway for genetic testing in UK NHS patients with cancer: BRCA-DIRECT randomised study internal pilot

Abstract: BackgroundGermline genetic testing affords multiple opportunities for women with breast cancer, however, current UK NHS models for delivery of germline genetic testing are clinician-intensive and only a minority of breast cancer cases access testing.MethodsWe designed a rapid, digital pathway, supported by a genetics specialist hotline, for delivery of germline testing of BRCA1/BRCA2/PALB2 (BRCA-testing), integrated into routine UK NHS breast cancer care. We piloted the pathway, as part of the larger BRCA-DIRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…After a median turnaround time of 44 days, clinical management was altered for 24 women with pathogenic variants (77%); fifteen were referred for consideration of bilateral or contralateral prophylactic mastectomy, eighteen for consideration of risk‐reducing salpingo‐oophorectomy. The high acceptability and low decision regret reported by the participants echo reports by similar mainstreaming initiatives elsewhere of uptake by as many as 98% of people with breast cancer offered testing at the time of diagnosis 8 …”
supporting
confidence: 66%
“…After a median turnaround time of 44 days, clinical management was altered for 24 women with pathogenic variants (77%); fifteen were referred for consideration of bilateral or contralateral prophylactic mastectomy, eighteen for consideration of risk‐reducing salpingo‐oophorectomy. The high acceptability and low decision regret reported by the participants echo reports by similar mainstreaming initiatives elsewhere of uptake by as many as 98% of people with breast cancer offered testing at the time of diagnosis 8 …”
supporting
confidence: 66%
“…As a result, approximately 97% of PV carriers remain unidentified . Newer strategies expanding the genetic testing landscape include (1) mainstreaming genetic testing at cancer diagnosis (available for OC and being piloted for BC) and (2) population genetic testing approaches. Population genetic testing is cost-effective in the Jewish population and the general population for the hereditary breast and ovarian cancer CSGs studied in this article .…”
Section: Discussionmentioning
confidence: 99%
“…11,15,25 It is not clear whether this is due to the immunologic abnormalities that accompany cancerous conditions. 26 However, it has been demonstrated that the tumor-mediated granulocyte colony-stimulating factors might disrupt neutrophil release, which could be associated with excess levels of neutrophils, inducing PG. 27 A recent study described that the cancerous myeloid clone and polymorphonuclear cells in neutrophilic dermatosis were observed to have a common clonal progenitor.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies directly reported cancer-associated mortality in PG, the current study aligned with studies that reported an association between them . It is not clear whether this is due to the immunologic abnormalities that accompany cancerous conditions . However, it has been demonstrated that the tumor-mediated granulocyte colony-stimulating factors might disrupt neutrophil release, which could be associated with excess levels of neutrophils, inducing PG .…”
Section: Discussionmentioning
confidence: 99%